Ameliorative effect of vitamin C on cypermethrin-induced hepatotoxicity and renal malfunction of adult male rats. - Kheirallah, Nessrin; Hussein, Hussein K.; Gawad, Horeya Abd El; Youssef, Basma (JOURNAL OF ADVANCES IN BIOLOGY, 2021)
Cypermethrin is a widely used insecticide belongs to type II pyrethroids. It is highly used in developing countries to control many species of insects as it plays an important role in pest control. Vitamin C is an important intracellular antioxidant against insecticides. The aim of the present study is to analyze the toxic effects of cypermethrin (CYP) and the positive effect of vitamin C (VC) with graded doses (0 CYP, 200 VC, 12 CYP and 12 CYP+200 VC mg/kg body weight of male rats/day) for 30 days on liver and kidney functions. Moreover, antioxidant enzymes, oxidative stress markers, glycogen and glucose levels and also serum lipid profile were studied. Also, this study aimed to evaluate the possible protective role of vitamin C against cypermethrin toxicity